Environmental components in poetic model: Palembang urban heat island case study - Zuber Angkasa; Fachrurrozie Sjarkowi; Dadang H Purnama; Dwi Setiawan; Ngakan Putu Sueca (Proceedings of AICS - Social Sciences, 2013)
Urbanization has opened urban thermal comfort zones thereby creating an urban island environment worldwide. Knowledge necessary to mitigate this phenomenon extend beyond knowledge on the city itself. This study sought to determine the role of environments in creating an urban heat island. A literature review was applied, to collect current knowledge on social, built, modified, and natural environment, in POETIC framework. The aim was to ascertain environmental components of urban heat island in Palembang city. The results indicated some environmental dimensions of urban heat island in Palembang. Social dimension consists of education level, people density in a house, and income level. Built dimension consists of distance between building, material albedo, material impermeability, building height, ventilations number, and ventilations area. Modified environment dimension consists of area of burning spot in open space, water pollution level, air pollution level, garden area, and green roof area. Natural environment consists of green open space area, vegetation density, and leaf area exposed to open space. Some hypotheses was developed and recommended for the further research.Keywords: Environment, POETIC model, Urban Heat Island